2014
DOI: 10.1371/journal.pone.0111815
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Proteoglycan-Induced Autoimmune Arthritis by Myeloid-Derived Suppressor Cells Generated In Vitro from Murine Bone Marrow

Abstract: BackgroundMyeloid-derived suppressor cells (MDSCs) are innate immune cells capable of suppressing T-cell responses. We previously reported the presence of MDSCs with a granulocytic phenotype in the synovial fluid (SF) of mice with proteoglycan (PG)-induced arthritis (PGIA), a T cell-dependent autoimmune model of rheumatoid arthritis (RA). However, the limited amount of SF-MDSCs precluded investigations into their therapeutic potential. The goals of this study were to develop an in vitro method for generating M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…The percentages of Th (CD4 + ) spleen cells containing intracellular cytokines or Foxp3 in cultures of antigen-stimulated spleen cells were determined by flow cytometry [28] on a BD FACS Canto II flow cytometer and analyzed using FACS Diva software (BD Flow Cytometry Systems, San Jose, CA). 3 …”
Section: Materials and Methods3mentioning
confidence: 99%
“…The percentages of Th (CD4 + ) spleen cells containing intracellular cytokines or Foxp3 in cultures of antigen-stimulated spleen cells were determined by flow cytometry [28] on a BD FACS Canto II flow cytometer and analyzed using FACS Diva software (BD Flow Cytometry Systems, San Jose, CA). 3 …”
Section: Materials and Methods3mentioning
confidence: 99%
“…In another study, heterogeneous populations of MDSCs generated from bone marrow precursors with GM-CSF, G-CSF and IL-6 suppressed autoimmunity in a proteoglycan induced model of arthritis. These cells suppressed T-cell proliferation through the production of nitric oxide (186). …”
Section: Introductionmentioning
confidence: 99%
“…Given the potent immuoregulatory activity of MDSCs, it could be expected that MDSCs could have therapeutic impact on RA. There have been discordant results regarding the effect of MDSCs on RA [12][13][14][15][16][17][18][19] . However, all the previous papers performed adoptive transfer of MDSCs in animal model of RA to verify whether the MDSCs had therapeutic effects on RA.…”
Section: Discussionmentioning
confidence: 99%
“…have therapeutic effects in animal model of RA [12][13][14][15][16] . However, a few recent papers have shown that MDSCs can aggravate inflammatory arthritis in mice [17][18][19] .…”
mentioning
confidence: 99%